2021
DOI: 10.1029/2020ja028716
|View full text |Cite
|
Sign up to set email alerts
|

The First Observation of N+ Electromagnetic Ion Cyclotron Waves

Abstract: Electromagnetic ion cyclotron waves are predominately left-hand circularly polarized waves with small wave normal angle (WNA), and with frequencies below the proton cyclotron frequency (Horne & Thorne, 1993). EMIC waves are usually generated near the Earth's equator and tend to become more oblique and linearly polarized during their propagation toward higher latitudes. In the inner magnetosphere, EMIC waves are generated preferentially in regions where hot (∼ 10-100 keV) ring current anisotropic ions and cold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 86 publications
(135 reference statements)
0
11
0
Order By: Relevance
“…Recently, it has been reported that the spectral properties of EMIC waves are also affected by other minor heavy ions such as nitrogen ions (N + ) and doubly charged oxygen ions (O 2+ ) in the terrestrial magnetosphere (Bashir & Ilie, 2018, 2021; Yu et al., 2021). The small fraction of heavy ion concentration changes the EMIC wave properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the spectral properties of EMIC waves are also affected by other minor heavy ions such as nitrogen ions (N + ) and doubly charged oxygen ions (O 2+ ) in the terrestrial magnetosphere (Bashir & Ilie, 2018, 2021; Yu et al., 2021). The small fraction of heavy ion concentration changes the EMIC wave properties.…”
Section: Introductionmentioning
confidence: 99%
“…Since H + , He + , and O + are the most common ion species observed in the background plasma, EMIC waves are often divided into three usual bands (H + , He + , and O + bands), the wave generation and wave properties of which have been investigated in a great number of studies. The effect of N + on EMIC waves has also been discussed in Bashir and Ilie (2018), and recent studies have reported the occurrence of N + band EMIC waves observed in the inner magnetosphere (Bashir & Ilie, 2021). To the best of our knowledge, however, the effects of O 2+ on EMIC waves and O 2+ band EMIC waves have not been studied yet.…”
Section: Discussionmentioning
confidence: 99%
“…However, besides He + and O + , other heavy ions exist in the magnetosphere, such as the nitrogen ions (N + ) and doubly charged oxygen ions (O 2+ ; Funsten et al., 2013; Vira et al., 2021; Young et al., 1977, 1982). Recent studies have demonstrated the effect of N + on EMIC waves and observed N + band EMIC waves in the inner magnetosphere (Bashir & Ilie, 2018, 2021). EMIC waves indicating the presence of M / Q = 2 ions in the terrestrial magnetosphere have also been observed (Engebretson et al., 2018; Lee et al., 2019; Miyoshi et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The propagation of EMIC waves to and across local crossover frequencies in a multi-ion plasma can allow waves to achieve linear or right-handed polarization. Thus, under certain assumptions on wave generation, wave properties from Fourier spectra and the possibility of crossover frequencies enabling mode-conversion during propagation have been used to infer the ion composition or presence of minor ion species in Earth's magnetosphere (Min et al, 2015;Miyoshi et al, 2019;Engebretson et al, 2018;Bashir and Ilie, 2021). Wave modeling and mode conversion at the bi-ion hybrid resonance has also been presented as a method to derive magnetospheric ion composition (E. H. Kim et al, 2015).…”
Section: Wave Propagationmentioning
confidence: 99%